Natural law, history and politics - Drane, James (Acta Bioethica, 2002)
The basic philosophical vision and ethical principles of Catholic Natural Law claim universality. Natural Law thinking aspires to objectivity and universality and at the same time is open to the continuing influence from history and politics. The background principles of positive law historically go by the name of Natural Law. Suffering and injustice contribute to a vision both of the structure of human existence and of what we mean by humane law and ethics. When we confront a cultural crisis, Natural Law, looks not to the past but to the future. Few people today talk of the ethical dimensions of social realities in terms of Natural Law. This is true both in the Church and in the State. In bioethics, the principles rooted in the universal structure of human life have to provide direction and regulations on the playing field of contemporary life and medicine. A liberal Catholic perspective tries to keep in play the universal and the particular aspects of Natural Law reasoning.